Novel G‐CSF conjugated anionic globular dendrimer: Preparation and biological activity assessment - Seyed Shahaboddin Mousavi Motlagh; Mohammad Seyedhamzeh; Reza Ahangari Cohan; Mehdi Shafiee Ardestani; Behrouz Vaziri; Kayhan Azadmanesh; Sahar Saberi; Vahideh Masoumi (Wiley, 2021)
Abstract The most crucial role of granulocyte colony‐stimulating factor (G‐CSF) in the body is to increase the strength of immune system. In recent years, research on the use of nanoparticles in pharmaceuticals has been considered, most of which have been for drug‐loading purposes. In this study, a novel G‐CSF conjugated dendrimer was synthesized and characterized using different techniques. In vitro cytotoxicity was assessed on A549 and L929 cells, while abnormal toxicity was studied in mice. In vitro and in vivo biological activities were assessed in NFS60 cells and rats, respectively. In addition, in vivo distribution, plasma half‐life, and histopathological effect were studied in rat. The characterization tests confirmed the successful conjugation. There was no difference between G‐CSF cytotoxicity before and after conjugation, and no difference with the control group. No mice showed abnormal toxicity. Although in vitro biological activity revealed both conjugated and free G‐CSF promote proliferation cells, biological activity decreased significantly after conjugation about one‐third of the unconjugated form. Nonetheless, in vivo biological activity of conjugated G‐CSF increased by more than 2.5‐fold relative to the unconjugated form, totally. Fortunately, no histopathologic adverse effect was observed in vital rat tissues. Also, in vivo distribution of the conjugate was similar to the native protein with an enhanced terminal half‐life. Our data revealed that G‐CSF conjugated dendrimer could be considered as a candidate to improve the in vivo biological activity of G‐CSF. Moreover, multivalent capability of the dendrimer may be used for other new potentials of G‐CSF in future perspectives.